EVALUATION OF BALANCE, PROPRIOCEPTION, AND PHYSICAL PERFORMANCE PARAMETERS OF SOCCER REFEREES IN DIFFERENT CLASSIFICATIONS - Gürol, Barış; Bingul, M. Kagan; Kizilet, Ali (Acta Scientiae et Intellectus, 2024)
The aim of this study is to examine the relationship between proprioception and balance values of soccer referees in different classifications and certain physical performance values. In the present study, 60 male soccer referees working at Turkish Football Federation were voluntarily involved. The referees were divided into 3 groups based on their classifications (national referees n=20, regional referees n=20, candidate referees n=20. The soccer referees were taken to anthropometry, proprioception (30°, 80°, and 130° angles of shoulder joint), balance, elasticity, jumping, and agility tests. One Way ANOVA test was implemented for data analysis. Post hoc Tukey test was used for investigating from which the intergroup different originated. The differences between national referees and second referees were examined using Mann Whitney U test. The elasticity test results were found to be 27.43±10.95 for national referees, 28.40±7.64 for regional referees, and 34.85±6.05 for candidate referees. The candidate referees were found to be statistically significantly more elastic than regional referees and national referees (p=0.015*). The agility test results were found to be 2.44±0.10 for national referees, 2.58±0.13 for regional referees, and 2.51±0.14 for candidate referees. The national referees were found to be statistically significantly more agile than regional referees (p=0.004*). In conclusion, it was determined that more frequently implemented agility and reaction exercises and having them a part of training offered the national referees a better agility times. Proprioception is an effective way of preventing the injuries. Proprioception exercises are believed to increase the environmental control and field perception of referees.